COMMUNICATION IN HOMO DEUS YUVAL NOAH HARARI - St. Shofiyah (Jurnal Jurnalisa: Jurnal Jurusan Jurnalistik, 2022)
One of the elements that build human civilization is how to support the communication dimension in each stage of the civilization, even though the communication aspects are part of civilization itself. Therefore, studying a civilization, we are studying the dimensions of communication in that life. A work by an Israeli historian, Yoval Noah Harari, is the study of this article. Homo Deus, one of Harari's trilogy of masterpieces, has long been the subject of public discussion, containing many controversies that have later invited some debates. An unusual book because it can review almost all aspects of human life. Each focus of the study is reviewed from various dimensions. Examined with an unusual blend, scientific and social meet in one work. Although the content of this book is very comprehensive, the author only examines it from one dimension, namely the communication dimension. Studying this book gives us information that the civilization of communication goes hand in hand with human civilization. There is a reciprocal relationship between human civilization and the dimensions of communication. Communication develops because of the broad path provided by civilization, civilization develops because of the support of communication, and communication itself is part of that civilization. Then this relationship became crippled when communication devices, software and hardware, accelerated beyond human civilization itself.